(untitled) (Academicia Globe: Inderscience Research, 2022)
Abdullah Qadiri’s works of art pay special attention to the use of cohesive parts, especially in the description of a person, an event, a situation. The author’s style of writing can be clearly defined by this feature. Everyone can tell that the image belongs to A. Kadyri: yigit ”.